2015
DOI: 10.3171/2014.9.jns141749
|View full text |Cite
|
Sign up to set email alerts
|

The Barrow Ruptured Aneurysm Trial: 6-year results

Abstract: obJect The authors report the 6-year results of the Barrow Ruptured Aneurysm Trial (BRAT). This ongoing randomized trial, with the final goal of a 10-year follow-up, compares the safety and efficacy of surgical clip occlusion and endovascular coil embolization in patients presenting with subarachnoid hemorrhage (SAH) from a ruptured aneurysm. The 1- and 3-year results of this trial have been previously reported. methods In total, 500 patients with an SAH met the entry criteria and were enrolled in the study. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
176
3
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 360 publications
(210 citation statements)
references
References 11 publications
11
176
3
13
Order By: Relevance
“…The International Subarachnoid Aneurysm Trial in 2015 indicated that these two methods were effective for the treatment of intracranial aneurysms (15). Currently, the surgical clipping of intracranial aneurysms is a popular treatment (16). Neurosurgical clipping can be affected by numerous factors, including the age and sex of the patient, the location and size of the aneurysm, and the extent of calcification or sclerosis of the aneurysm and parent artery (14).…”
Section: Discussionmentioning
confidence: 99%
“…The International Subarachnoid Aneurysm Trial in 2015 indicated that these two methods were effective for the treatment of intracranial aneurysms (15). Currently, the surgical clipping of intracranial aneurysms is a popular treatment (16). Neurosurgical clipping can be affected by numerous factors, including the age and sex of the patient, the location and size of the aneurysm, and the extent of calcification or sclerosis of the aneurysm and parent artery (14).…”
Section: Discussionmentioning
confidence: 99%
“…Эндова-скулярная окклюзия является предпочтительной даже в тех случаях, когда анатомические условия не позволяют выключить аневризму полностью. В этих условиях частичная окклюзия аневризмы может снизить риск повторного разрыва и создать условия для безопасного проведения консервативной тера-пии [7]. Радикальное микрохирургическое вмеша-тельство может быть проведено вторым этапом в холодном периоде после стабилизации состояния больного.…”
Section: топографоанатомические особенности аневризмыunclassified
“…При этом существует опре-деленная конкуренция между этими направления-ми, что может приводить к недостаточно обосно-ванному использованию или, напротив, неисполь-зованию того или иного метода. Между тем много-численные публикации свидетельствуют о том, что ни микрохирургия, ни эндовазальная хирургия не могут самостоятельно решить все сложные пробле-мы хирургического лечения больных с разорвавши-мися аневризмами [1][2][3][4][5][6][7][8]. В этой связи поиск опти-мального выбора лечения и путей кооперации раз-личных методов не теряет своей актуальности.…”
unclassified
“…A case was made for surgical treatment for anterior circulation aneurysms, given the similar outcomes, higher obliteration rate (98 vs. 48 %), lower retreatment rate (4 vs. 13 %), and high crossover from the coil to clip arm (38 %). For posterior circulation aneurysms, outcomes were definitely better for endovascular [11].…”
mentioning
confidence: 99%
“…A significant number of aneurysms are still treated with surgical clipping in a more efficacious and long-lasting manner. On a paper presented at the AANS meeting earlier this year [11], Spetzler et al discussed the 6-year results of the BRAT study. A case was made for surgical treatment for anterior circulation aneurysms, given the similar outcomes, higher obliteration rate (98 vs. 48 %), lower retreatment rate (4 vs. 13 %), and high crossover from the coil to clip arm (38 %).…”
mentioning
confidence: 99%